INNOVATIVE FINANCING SCHEMES FOR AGRICULTURAL INFRASTRUCTURE: OVERCOMING LOCAL FISCAL CONSTRAINTS THROUGH INTER-GOVERNMENTAL COLLABORATION (A CASE STUDY OF BIREUEN REGENCY) - Syamsil Adri (Jurnal Ikhtibar Nusantara, 2026)
Abstract Achieving food self-sufficiency in Bireuen Regency currently faces a severe policy deadlock. Following the late-2025 floods, 4,731 hectares of productive rice fields and vital infrastructure, such as the Pante Lhong and Hagu Peudada dams, suffered massive damage. The root cause is a local fiscal "double burden"; the regional budget is locked into housing recovery while agricultural infrastructure needs reach IDR 1.1 Trillion. This policy paper aims to formulate an innovative financing scheme to overcome the authority barriers of Law 23/2014. Using a qualitative-case study methodology with IFE, EFE, and SWOT quadrant analysis, Bireuen was found to be in a Turnaround position. The results of William Dunn’s criteria analysis recommend the issuance of a Regent's Regulation on the Cross-Level Government Funding Collaboration Scheme as the most logical single solution. Through a Cooperation Agreement (PKS) referencing Presidential Instruction 2/2025, regional fiscal constraints can be breached by securing APBN and APBA support. This policy is not merely an administrative matter; it is a humanitarian effort to restore the dignity and livelihoods of thousands of Bireuen farmers from the threat of post-disaster poverty. Keywords: Innovative Financing, Agricultural Infrastructure, Collaboration, Disaster, Bireuen.